2021
DOI: 10.1088/1742-6596/2120/1/012004
|View full text |Cite
|
Sign up to set email alerts
|

FTIR spectroscopy characterization and critical comparison of poly(vinyl)alcohol and natural hydroxyapatite derived from fish bone composite for bone-scaffold

Abstract: This paper presents the interaction comparison of poly(vinyl) alcohol (PVA) with hydroxyapatite derived from Spanish Mackerel (SM) and Whitefin Wolf Herring (WWH) bones, in different processing method. PVA filament and solution casting method illustrated higher crystallinity in the FTIR graph as compared to the PVA pellet and filament extrusion method. Besides, minimal interactions between PVA with glycerol and HAp was observed as well. PVA pellet and solution casting method portrait higher interaction as comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…The FTIR results identified that the functional group indicates O—H stretching, which confirmed eggshell HAp, EGCG, and HPMC, similar to the results of Rogina et al, that indicated hydrogel composite at 3,150–3,600 cm −1 wavenumbers ( Rogina et al, 2019 ). The evidence of strong PO 4 3- groups which confirmed HAp was 1040 cm −1 and 1090 cm −1 ( Hooi et al, 2021 ) but following the study of Siswanto et al (2020) , PO4 3- was also identified the bending of PO 4 3- at 500 cm −1 to 630 cm −1 that also proved of HAp existance, it supports this study that had phosphate bending at 559.96 cm -1 to 602.17 cm −1 .…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The FTIR results identified that the functional group indicates O—H stretching, which confirmed eggshell HAp, EGCG, and HPMC, similar to the results of Rogina et al, that indicated hydrogel composite at 3,150–3,600 cm −1 wavenumbers ( Rogina et al, 2019 ). The evidence of strong PO 4 3- groups which confirmed HAp was 1040 cm −1 and 1090 cm −1 ( Hooi et al, 2021 ) but following the study of Siswanto et al (2020) , PO4 3- was also identified the bending of PO 4 3- at 500 cm −1 to 630 cm −1 that also proved of HAp existance, it supports this study that had phosphate bending at 559.96 cm -1 to 602.17 cm −1 .…”
Section: Discussionsupporting
confidence: 77%
“…All Ca/P ratio of the samples was above the stochiometric (1.67), and the HAp-Col-EGCG scaffold with 4 % HAp was the nearest to 1.67. The higher Ca/P ratio presents due to higher HAp concentration, it indicated the existence of B-type carbonate phosphate which identical with a mineral in human bones that promotes cell adhesion ( Hooi et al, 2021 ). Higher Ca/P ratio will support the smaller particle size so the degradation in the living body facilitated so the Ca and P component will absorb faster.…”
Section: Discussionmentioning
confidence: 99%
“…The functional groups present in the composites were determined with the aid of an FTIR spectrophotometer. The FTIR of the resin, cow bone, and kaolin were examined in order to draw important conclusions based on the kinds of interactions present in the composites made with different filler compositions 54–56 . The FTIR spectrum of the calcined cow bone (CB 100 ) is given in Figure 2a.…”
Section: Resultsmentioning
confidence: 99%
“…The FTIR of the resin, cow bone, and kaolin were examined in order to draw important conclusions based on the kinds of interactions present in the composites made with different filler compositions. [54][55][56] The FTIR spectrum of the calcined cow bone (CB 100 ) is given in Figure 2a. The peak at 872 cm À1 can be attributed to the presence of an alkene hydrogen in bending mode.…”
Section: Functional Group Determinationmentioning
confidence: 99%
“…40 The influence of glycerol on the hydrogel structure was further evidenced by the appearance of additional peaks at 1043 cm −1 (Figure S4). 53 It is important to highlight that PVA contains relatively few primary alcohol groups, whereas glycerol primarily consists of primary alcohols. 49 The observed shifts in the C−C−O peak, characteristic of primary alcohols, provide a means to track the hydrogen bonding within the hydrogel.…”
mentioning
confidence: 99%